MATH SOLVE

3 months ago

Q:
# Given the functions f and g below, find g(f(dalecof(x) = (3x +1g(x) = x2 + 4x + 6

Accepted Solution

A:

Hello. To do this, we need to work from right to left. (Another way to phrase it is from inside to out). Step by step: 1). f(x)= 3x+1 2). Take 3x+1 and plug it into wherever you see the variable x in the g(x). ** g(f(x))= (3x+1)² + 4(3x+1) +6 g(f(x))= (3x+1)² + 12x + 4 + 6 g(f(x))= (3x+1)² + 12x + 10 g(f(x))= (3x+1)(3x+1) + 12x + 10g(f(x))= 9x² + 6x +1 + 12x +10 g(f(x))= 9x² + 18x + 11 Hope that helped. ** this is not proper notation, but rather, a demonstration of how plugging functions into functions would work. ************************ Disclaimer: Always double check your answer with a reliable source, as mistakes can be made.